Bulacan Agricultural State Colleges (BASC) campus design visions of redevelopment in an agropolitan context - Villanueva, Cecilia S. (College of Architecture, University of the Philippines Diliman, 2008)
Campus architecture for agricultural colleges such as Bulacan Agricultural State College (BASC) accommodates spaces for food production and learning activities. The arrangement and ordering of forms and spaces also determine how architecture might promote endeavors, elicit responses, and communicate meaning. Form and space are presented not as ends in themselves but as a means to solve a problem in response to conditions of function, purpose, and context (Ching, 1996 p.IX) in the built environment. Campus plans and facade elements can insight and convey a college's vision. The ability to recognize the basic elements of form and space and understand how they can be manipulated and organized in the development of a conceptual plan and images are vital issues (Ching, 1996)that surround the proposed BASC campus redevelopment plan. The increase of enrollment in BASC calls for massive improvement and development of physical facilities. to be able to cater to the greater demand of tertiary education. A sizeable area of the campus where new building facilities are proposed to be located is an existing residential community. State universities and colleges (SUC) are now required to generate their own income by maximizing the potentials of the large tract of land allocated fro their utilization. Government subsidies are decreases annually to further motivate SUC to productivity manage resources that are inherent in their domain. How should these issues now be approached? What is the plausible approach in campus design with the presence of existing community settlements in the proposed BASC Development Plan? [Campus] + [(Design Approach and Strategies)] = Visions of Redevelopment. BASC Campus Redevelopment plan presents a bilateral approach in campus design where visions of redevelopment in an agropolitan context formulate a strategic framework in addressing the college's vision for excellence. Most campus designs are confronted with specific issues that require specific approaches and strategies. BASC's campus design presents a comprehensive framework that can be adopted in other agricultural schools or any school in addressing a holistic approach in academic excellence and campus redevelopment. Through agropolitan planning a balance between agricultural land-use and built-up spaces was achieved through comparative analysis of case studies. Proposed residential facilities for teaching and non-teaching staff community shall coexist with proposed tertiary education facilities through analyzing topography, current patterns of land use and other relevant factors. A creative means of segregating without isolating these different land uses would be to provide strategically located transitional buffer zones so as to diminish traffic & noise and heighten a creative landscape in the campus periphery. Visions of BASC redevelopment is a showcase of unique Filipino agriculture and rustic living as manifested in design through images of facade, landscape and landmarks. The proposed landscape of BASC requires major modification of the existing character of the landscape (U.S. Bureau of Land Management, 2008). The level of change to the characteristic landscape is high so as to attain the vision of BASC. The proposed redevelopment landscape of BASC showcases unique Filipino agriculture such as freshwater aquatic farming, various floral nurseries and production gardens, mango and other fruit orchards among others. The site also features a dramatic view of Central Luzon Plains with some delicate changes in terrain. The proposed redevelopment plan is ideal for promoting an Agro-tourism program.